Fragmentation of International Trade Law Reassessed Analyzing the Role of PTA-DSMs Based on Their Adjudication of General Exception Clauses - Wasilczyk, Patrick (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book provides innovative and empirically based insights into the ongoing debate on the fragmentation of international trade law. It offers the reader a much-needed doctrinal overview of the different approaches to the issue of fragmentation and reveals their inherent methodological advantages and limitations. On this basis, the book then approaches the issue of fragmentation from an empirical standpoint by applying a novel dataset on Preferential Trade Agreements' Dispute Settlement Mechanisms (PTA-DSMs), which have been used to adjudicate general exception clauses within the context of the individual PTA Members' obligation to liberalize trade in goods. Although the results remain limited to the single issue of PTA-DSM adjudication for liberalization of trade in goods, they are indicative of key misconceptions regarding the fragmentation of ITL. As the findings confirm, the PTA-DSMs assessed have ultimately come to equivalent decisions, taking into consideration their overall use, the nature of the legal commitments embedded in the respective PTAs, and the economic wellbeing of the respective PTA partners. The book reveals the influence of specific PTA-DSMs on other PTA-DSMs and thereby paves the way for legal unification, rather than fragmentation.
1. Introduction -- 2 Fragmentation of International Trade Law due to the activity of PTA-DSMs. -3. Revisiting methodological shortcomings for assessing the role of PTA-DSMs for the fragmentation of international trade law -- 4. Developing the Ramifications for the Analysis on the Contribution of Active PTA-DSMs to the Diversity in the Regulation of International Trade -- 5. Putting the revisited methodology to practice -- 6. Results on PTA-DSMs' role for the fragmentation of international trade law -- 7. General conclusion.8. Annex -- 9. Bibliography.
Keywords: International law; Trade regulation; International economic relations; International Economic Law, Trade Law; International Economics